USULAN PENGGUNAAN SIX SIGMA UNTUK PENINGKATAN KUALITAS PROSES PRODUKSI DI PT. A O - SAHAT SINAMBELA; ABDUL HARIS LAHUDIN (LPPM, 2014)
The importance of quality to maintain market share/customer on a tight industrial competition today, it would require quality improvement continuously by reducing variation in the process output. Improving quality with Six Sigma method is very appropriate to be applied to reducing output variation process YNA in PT. AO. With the concept of Six Sigma by approach define, measure, analyze, improvement, and control (DMAIC), obtained CTQ’s which became the cause of defective components opportunity YNA. There are ten (10) opportunity quality characteristic: body edge is not rough, body is not crack, body lips are not curve, body texture shall symmetric, handhold is not crack, handhold is cut straight, head of handhold is not curve, edge of bracket not rough, holes at bracket not too large. The value of Six Sigma capability in that Company is 3,86, with the value of DPMO, 9,12 this indicating that company is for from word class company peat reach capability five to Six Sigma. Process Improvement DMAIC approach are done by exact time and right way, by road map PDCA concept and by, application of control chart (SPC). Keywords: Improved quality of Six Sigma, machining Processes, DMAIC, FMEA,